Marketing Communication Strategies In Building Corporate Brand Image: A Study Of Mvp.Co As A Clothing Industry Brand In Bengkulu City - Bintara Santika Putra (Universitas Dehasen Bengkulu, 2026)
This research aims to analyze the marketing communication strategies implemented by MVP.CO in building its brand image as a clothing industry brand in Bengkulu City. The study focuses on the application of the 7P marketing mix, product, price, place, promotion, people, process, and physical evidence as well as the SWOT analysis used to identify internal strengths and weaknesses along with external opportunities and threats. Employing a qualitative descriptive approach, data were collected through in-depth interviews, observation, and documentation. The findings indicate that MVP.CO effectively applies the 7P marketing mix by offering premium-quality products, competitive pricing, strategic distribution channels, and dynamic promotional activities supported by competent human resources and structured operational processes. The SWOT analysis further shows that MVP.CO possesses significant internal strengths and opportunities to enhance its competitive position, although it must address several weaknesses, particularly in digital promotion, facility development, and production capacity. Overall, this research concludes that integrated marketing communication strategies play an essential role in strengthening MVP.CO’s brand image within the creative clothing industry in Bengkulu.